Phytochemical studies on daun kadok (Piper sarmentosum) / Khong Heng Yen ... [et al.]. - Khong, Heng Yen; Ahmad, Fasihuddin; Nyokat, Nyotia (2004)
A phytochemical studies on the leaves of 'Daun Kadok' (Piper sarmentosum) was carried out. The sample was macerated in hexane followed by ethyl acetate and methanol to afford the crude extracts. The crude methanolic extract was then purified lIsing chromatography techniques to afford asarone (2,4,5- trimethoxypropenylbenzene). The structure of this compound was determined by spectroscopic methods such as Gas chromatography-mass spectroscopy (GC-MS), infrared (rR) and nuclear magnetic resonance (' H NMR).